Sarcoidosis-Lymphoma Syndrome: The Impact of Isolated Splenic Sarcoidosis - Piteira, Ana Rita; Carrega, Filipa; Silvério, Rita; Fera, Manuela; Pedroso, Ermelinda (International Journal of Innovative Research in Medical Science, 2023)
Sarcoidosis is a systemic inflammatory disease of unknown etiology, characterized by non-necrotizing granuloma formation in multiples organs. Isolated extrathoracic sarcoidosis has been reported in under 10% of the patients, and so isolated spleen sarcoidosis is extremely rare. A 68-year-old woman presented to our hospital with 6-month history of anorexia, left hypochondrial discomfort and early satiety, aggravated with high fever, fatigue and generalized myalgia two days before coming to the hospital. The physical examination detected splenomegaly. Laboratory analysis revealed pancytopenia with hemolysis and an elevated angiotensin converting enzyme. Image studies showed splenomegaly with multiple hypoechoic lesions. Infectious and autoimmune etiology was excluded. Bone marrow biopsy excluded lymphoproliferative disease. Patient underwent ultrasonography-guided spleen biopsy finding noncaseating epithelioid cell granulomas. The patient was started on corticosteroids with symptom improvement. Two years after the diagnosis the pancytopenia recurred, and bone marrow biopsy was repeated revealing non-Hodgkin lymphoma infiltration. Although splenic sarcoidosis was treated and the regular follow-up of the patient it was impossible to predict the development of lymphoma as it is still unknown what is the cause effect link between sarcoidosis and lymphoma.